Site location and techno-economic analysis of utility-scale concentrating solar power plants in South Africa - Brodrick, Joshua JL (Energy Research Centre, 2014)
This dissertation comprises a two-part study concerned with the identification and quantification of potential Concentrating Solar Power (CSP) sites in South Africa; and the performance and cost modelling, optimisation and analysis of two CSP technologies in three locations. A further theme of the study is the consideration of the availability of water for plant cooling purposes, and hence the comparison between, and analysis of optimal CSP technologies and cooling methods for each location.